"Displacing the Productionist Paradigm: A Comment on Paul Thompson's Spirit of the Soil, 2nd Edition.". Issue 3 (2nd September 2019) - Wolf, Clark
ABSTRACT: Paul Thompson's book The Spirit of the Soil first appeared in 1995, and has been re-issued in a new edition in 2017. This comment on the new edition addresses Thompson's argument concerning the productionist paradigm in contemporary agriculture. Thompson's work implies that overproduction is the result of passive acceptance of an ethic of production, which has historical, sociological, and religious cultural roots. This article interprets Thompson's discussion of productionism as an argument for the best explanation, and offers an alternative explanation for overproduction in American agriculture. The claim is not that Thompson's argument is wrong, but that it is incomplete. But a proper understanding of the sources of productionism is important, since our understanding of the problem will inform the development of interventions designed to address it.